Triple Inhaler versus Dual Bronchodilator Therapy in COPD: Real-World Effectiveness on Mortality - Suissa, Samy; Dell'Aniello, Sophie; Ernst, Pierre (Chronic obstructive pulmonary disease, 2022)
Randomized trials of triple therapy including an inhaled corticosteroid (ICS) for chronic obstructive pulmonary disease (COPD) reported remarkable benefits on mortality compared with dual bronchodilators, likely resulting from ICS withdrawal at randomization. We compared triple therapy with dual bronchodilator combinations on major COPD outcomes in a real-world clinical practice setting. We identified a cohort of COPD patients, age 50 or older, treated during 2002-2018, from the United Kingdom's Clinical Practice Research Datalink. Patients initiating treatment with a long-acting muscarinic antagonist (LAMA), a long-acting beta 2 -agonist (LABA) and an ICS on the same day, were compared with patients initiating a LAMA and LABA, weighted by fine stratification of propensity scores. Subjects were followed-up one year for all-cause mortality, severe exacerbation and pneumonia. The cohort included 117,729 new-users of LAMA-LABA-ICS and 26,666 of LAMA-LABA. The adjusted hazard ratio (HR) of all-cause mortality with LAMA-LABA-ICS compared with LAMA-LABA was 1.17 (95% CI: 1.04-1.31) while for severe exacerbation and pneumonia it was 1.19 (1.08-1.32) and 1.29 (1.16-1.45) respectively. However, mortality was not elevated with triple therapy among patients with asthma diagnosis (HR 0.99; 95% CI: 0.74-1.34), with two or more prior exacerbations (HR 0.88; 95% CI: 0.70-1.11), and with FEV 1 percent predicted >30%. In a real-world setting of COPD treatment, triple therapy initiation was not more effective than dual bronchodilators at preventing all-cause mortality and severe COPD exacerbations. Triple therapy may be unsafe among patients without prior exacerbations, in whom ICS are not recommended, with no asthma diagnosis and with very severe airflow obstruction. Supplemental data for this article is available online at https://doi.org/10.1080/15412555.2021.1977789 .